Analisis Manajemen Risiko Usaha Berdasarkan ISO 31000 pada UMKM Annisa Toys di Kabupaten Bandung - Asep Rizal Maulana; Muhammad Luthfi Mubarrok; Muhamad Zaki; Panji Setia Meijaya; Muhammad Shoffan Anbiya; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy, particularly in the creative industry sector. One MSME operating in this sector is Annisa Toys, a doll production and retail business located in Kampung Boneka Sayati, Bandung Regency. Although Annisa Toys has been established since 1UU2 and has experienced significant business growth, various business risks remain and may affect its operational continuity and sustainability. This study aims to identify the business risks faced by Annisa Toys, analyze the level of risk based on the ISO 31000 framework, and formulate appropriate risk mitigation strategies. This research employs a descriptive qualitative approach, with data collected through direct observation, interviews with the business owner, and documentation studies. The results indicate that Annisa Toys faces several major risk categories, including operational risk, financial risk, human resource risk, market risk, marketing risk, and legal risk. Operational and market risks are identified as the most significant threats, particularly those related to custom doll production processes, intense price competition, and changes in consumer behavior. The implementation of ISO 31000–based risk management is expected to help Annisa Toys minimize risk impacts, improve operational efficiency, and maintain business sustainability in the increasingly competitive doll industry.